Molecular cloning and nucleotide sequence of a DNA fragment from Bacillus natto that enhances production of extracellular proteases and levansucrase in Bacillus subtilis. - Nagami, Y (1986)
A DNA fragment from Bacillus natto IFO3936 has been cloned which enhances the production of both extracellular alkaline and neutral proteases in Bacillus subtilis. The DNA sequence analysis around the gene responsible for the hyperproduction, prtR, revealed one open reading frame (comprising 60 amino acid residues) which was bounded by potential transcriptional and translational regulatory signals in its preceding and following regions. This open reading frame was not homologous to the published sequences of the structural genes of the two proteases. The calculated molecular weight (7,109) of the polypeptide predicted from the DNA sequence is much smaller than those of the two proteases, indicating that the gene product is distinct from those enzymes. In-frame fusion between the N-terminal region of the coding sequence and the lacZ gene of Escherichia coli demonstrated that the coding region was indeed translated in vivo. By deletion analysis it was suggested that prtR was the structural gene for the 60-amino-acid polypeptide. Cells carrying a prtR plasmid secreted both proteases 40 to 400 times more than the cells carrying the vector alone. Furthermore, it was found that prtR also enhanced the production of levansucrase by 1 or 2 orders of magnitude. There was no difference, however, in the amount of the other extracellular enzymes such as alpha-amylase, RNase, and alkaline phosphatase. These results indicate that prtR is specific for the hyperproduction of the proteases and levansucrase.